Front‐Line innovation: Rapid implementation of a nurse‐driven protocol for care of outpatients with COVID‐19. Issue 11 (8th March 2021) - Driver, Jane A.; Strymish, Judith; Clement, Sherry; Hayes, Barbara; Craig, Kathleen; Cervera, Alejandra; Morreale‐Karl, Michelle; Linsenmeyer, Katherine; Grudberg, Sarah; Davidson, Heather; Spencer, Jacqueline; Kind, Amy H. J.; et al.
Abstract: Aims and objectives: Our objective was to rapidly adapt and scale a registered nurse‐driven Coordinated Transitional Care (C‐TraC) programme to provide intensive home monitoring and optimise care for outpatient Veterans with COVID‐19 in a large urban Unites States healthcare system. Background: Our diffuse primary care network had no existing model of care by which to provide coordinated result tracking and monitoring of outpatients with COVID‐19. Design: Quality improvement implementation project. Methods: We used the Replicating Effective Programs model to guide implementation, iterative Plan‐Do‐Study‐Act cycles and SQUIRE reporting guidelines. Two transitional care registered nurses, and a geriatrician medical director developed a protocol that included detailed initial assessment, overnight delivery of monitoring equipment and phone‐based follow‐up tailored to risk level and symptom severity. We tripled programme capacity in time for the surge of cases by training Primary Care registered nurses. Results: Between 23 March and 15 May 2020, 120 Veterans with COVID‐19 were enrolled for outpatient monitoring; over one‐third were aged 65 years or older, and 70% had medical conditions associated with poor COVID‐19 outcomes. All Veterans received an initial call within a few hours of the laboratory reporting positive results. The mean length of follow‐up was 8.1 days, with an average of 4.2 nurse and 1.3 physician or advanced practice clinician contacts per patient. The majority (85%) were managed entirely in the outpatient setting. After the surge, the model was disseminated to individual primary care teams through educational sessions. Conclusion: A model based on experienced registered nurses can provide comprehensive, effective and sustainable outpatient monitoring to high‐risk populations with COVID‐19.